Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1523/jneurosci.1688-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Dysregulation and Infertility in Mice Lacking the Homeodomain Protein Six6

Abstract: The hypothalamus, pituitary, and gonads coordinate to direct the development and regulation of reproductive function in mammals. Control of the hypothalamic–pituitary– gonadal axis is dependent on correct migration of gonadotropin-releasing hormone (GnRH) neurons from the nasal placode to the hypothalamus, followed by proper synthesis and pulsatile secretion of GnRH, functions absent in patients with hypogonadal hypogonadism. In this study, we identify sine oculis-related homeobox 6 (Six6) as a novel factor ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 67 publications
7
73
0
Order By: Relevance
“…Procedures for pubertal onset, embryo collection and fertility assessment were performed as described in detail previously [19, 32, 33]. For fertility assays, 8-week-old Otx2:Lhrh-cre mice were housed with Otx2-flox/flox mice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Procedures for pubertal onset, embryo collection and fertility assessment were performed as described in detail previously [19, 32, 33]. For fertility assays, 8-week-old Otx2:Lhrh-cre mice were housed with Otx2-flox/flox mice.…”
Section: Methodsmentioning
confidence: 99%
“…Single immunohistochemistry and quantitative RT-PCR were performed as previously described [11, 19]. For double immunohistochemistry, the same protocol as for single immunohistochemistry was used, with the modification that after developing and imagine the anti-CRE (1/1,000) staining using Impact DAB (brown), the slides were washed in PBS-Tween 0.02%, followed by 5 min in denaturing solution (Biocare #DNS001), after which the sections were blocked in 5% goat serum and Avidin-Biotin solutions (Vector Labs), and the anti-LHRH (1/1,000) antibody was applied O/N following the regular immunohistochemistry protocol, using Impact VIP (purple) to visualize GnRH expressing cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Givens et al (2005) found evidence to support the role of DLX1 in regulating the GnRH promoter during development in mice. Several recent studies have associated the misexpression of GnRH with infertility in mice (Larder et al, 2011). DLX1 might therefore be associated with the rose comb phenotype and/or the subfertility linked to this trait.…”
Section: Mendelian Traits In Traditional and Village Chickens D Wraggmentioning
confidence: 99%
“…For instance, mice carrying a dominant-negative form of erbB4 targeted to astrocytes have a delayed first ovulation, but exhibit normal adult reproductive capacity (7). Additional examples are mice carrying a point mutation of the erbB1 receptor (30,31) and mice lacking the Janus-activated kinase 2 in GnRH neurons (32) or lacking the homeodomain protein Six6 also in GnRH neurons (33). The most tenable explanation for the absence of complete infertility resulting from these deficiencies is the existence of redundant and compensatory circuits that become operative when one system fails to perform.…”
Section: Discussionmentioning
confidence: 99%